The Speaking Space: Social Distinctions in Modern Kharkiv - Боженко, Анастасія (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences, 2018)
The article is devoted to the studying of interaction between physical and social space of Kharkiv in the second half of XIX – the early XX century. The main theoretical frame is the conception of Pierre Burdeau about social distinctions. The problems of the perception of separate peripheral areas as city space in guides and official documentationare highlighted; the results of censusare analyzed. The author studies the social zoning of modern Kharkiv, the marking of prestigious districts and the representation of power by elites in Kharkiv physic space.